DIRECTED READING-THINKING ACTIVITY (DRTA) STRATEGY IN READING CLASS AT SMA NEGERI 2 KOTA TERNATE - Safitri Lambutu; Naniek Jusnita; Susana R. Bahara (Universitas Khairun, 2023)
This study aims to determine whether the Directed Reading Thinking Activity (DRTA) strategy can improve students' reading comprehension at SMA Negeri 2 Kota Ternate. The research method used is pre-experimental design. Which consists of pre-test, treatment, and post-test design. The population in this study were students of class X-G SMA Negeri 2 Kota Ternate. Using a convenience sampling technique involving one X-G class. as the sample, 30 students at class. The results of the study show that the Directed Reading Thinking Activity (DRTA) strategy can improve students' reading comprehension in Class X-G at SMA Negeri 2 Kota Ternate. It is proven that the Pre-Test score is 48.73 and the Post-Test value is 68.77. Based on the difference in scores obtained by students in reading comprehension, it showed an increase from the pre-test to the post-test where the increase in students' reading comprehension increased. Significant improvement in student achievement. Thus, the null hypothesis (H0) is not accepted, while the alternative hypothesis (Hi) is accepted. Therefore the researcher concluded that. The Directed Reading Thinking Activity (DRTA) strategy is effective in learning reading comprehension. because students understand more easily with predictions that identify main ideas and supporting details and can be seen from the results of better student reading scores.